Implementasi Pupuk Cair Organik Masaro Terhadap Produktivitas Jagung Manis di Sabah Balau - Nury, Dennis Farina; Satria , Arysca Wisnu; Deviany, Deviany; Mustafa , Mustafa; Abidin, Akhmad Zainal (Politeknik ATI Padang, 2023)
This community service activity aims to increase corn production in Sabah Balau using POCI (Special Liquid Organic Fertilizer) products from Masaro. POCI is used as an organic fertilizer and its farming produces a higher production number, higher quality product, faster production rate while its production cost is lower. On the other hand, the problem of Indonesia is that national agriculture is stuck in inorganic chemical fertilization that has an impact on accelerating the degradation of agricultural land fertility. This matter can occur due to various problems, especially the culture of using chemical fertilizers that have been going on for too long. The activities carried out include socializing about recycling organic waste with POCI Masaro, conducting outreach activities about the benefits of POCI Masaro and practicing composting for corns. The results showed the enthusiasm of the community in participating to make POCI Masaro and demonstration plots. The output of this activity: Increased corn production, increased of knowledge and skills of community in making and applying POCI Masaro on plant and motivation of farmers to independently develop alternative organic fertilizers that are in accordance with farmers' needs.